1995
DOI: 10.1016/0014-5793(95)00986-j
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia prolongs neutrophil survival in vitro

Abstract: ~,bstract Neutrophil apoptosis represents a major mechanism ~nvolved in the resolution of inflammation. Since hypoxia induces apoptosis in several cell lines and is of particular relevance in many disease states, we studied the effect of oxygen concentration on neutrophil survival in vitro. Hypoxia caused a dramatic decrease in neutrophil apoptosis (% apoptosis 20 h: 78.7 + 2.2% in 21% 0 2, 61.4 _+ 6.5% in 2.5% 02, 23.1 + 3.2% in 0% 02, = 5). This was additive to the effect of GM-CSF (50 Ulml), not associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(136 citation statements)
references
References 43 publications
7
128
0
1
Order By: Relevance
“…A mitochondrial contribution to this activity cannot be ruled out. Finally, it is established that neutrophil-derived reactive oxidant species can regulate the progression of these cells into apoptosis (45)(46)(47). Oxidants derived from either NADPH oxidase or mitochondria may be involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…A mitochondrial contribution to this activity cannot be ruled out. Finally, it is established that neutrophil-derived reactive oxidant species can regulate the progression of these cells into apoptosis (45)(46)(47). Oxidants derived from either NADPH oxidase or mitochondria may be involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, constitutive neutrophil apoptosis is delayed under hypoxic conditions (46) and in neutrophils from chronic granulomatous disease patients (45). ROI production is not, however, inevitably linked to acceleration of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…One characteristic feature of advanced solid tumors is hypoxia. In fact, hypoxia promotes HIF-1a-dependent neutrophil survival (44,45) but impairs the respiratory burst activity in human neutrophils (46). In addition, it has been reported that blockade of TGFb in the tumor microenvironment drives neutrophil polarization from a protumoral "N2" phenotype to an antitumoral "N1" phenotype characterized by enhanced cytotoxic and immunostimulatory activities (47).…”
Section: Ly6gmentioning
confidence: 99%